Scenario of Manufacturing Pharmaceutical Small and Medium Enterprises(SMEs) in Pakistan - Muhammad Wasim, Jan Khan (IJBMES, 2014)
Small and medium enterprises of the whole world today, constitute more than 90% of the whole business entities throughout the world. Small and medium enterprises play a tremendous role in any economy like Pakistan as Pakistan is strategically located on the most important trade route between Asia and Europe. In Pakistan economy the manufacturing small and medium enterprises contribute more to the Pakistan’s economy. As the pharmaceutical industry in today’s world is an important and fundamental sector and is considered as a basic necessity in any locality of the globe. But one third of the whole population of the world at present do not access to the basic drugs of life. At the same time majority of the pharmaceutical industry of Pakistan comprise of small and medium enterprises and unfortunately face serious threats and simultaneously the empirical research in this sector is at initial stages.